Harmonization of cultural diversity and its role in achieving change management objectives in the Greater Salt Municipality - Alkhlaifat, Abdalrazzaq Yousef Abdalfattah (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of this research is to identify the relevance of cultural diversity and its role in achieving the objectives of change management in the Greater Salt Municipality, and the research sample consisted of (27) respondents from administrators and workers in the following sections: The Cultural Department, the Public Relations Department, the Human Resources Department, and the General Bureau Department in the Greater Salt Municipality. To achieve the objectives of the study, the descriptive and analytical approach was followed.The research reached a number of results, the most important of which is that there is a good degree of agreement among the members of the study sample to measure the compatibility of the cultural diversity of the workers in the Greater Salt Municipality. The research also concluded that there is a good degree of agreement and a good degree of agreement between the study sample members of the role of the following sections: The Cultural Department. And the Public Relations Department, the Human Resources Department, and the General Office Department, in the Greater Salt Municipality in the success of Change Management. The research also found that there is a statistically significant relationship between the harmonization of cultural diversity and its role in achieving the objectives of change management in the Greater Salt Municipality and that there is a statistically significant relationship between each of (harmonizing ethnic diversity, harmonizing sexual diversity, and harmonizing age diversity) and achieving goals Managing Change in the Greater Salt Municipality.
Keywords: cultural diversity; change management; Greater Salt Municipality; age diversity; ethnic diversity; sexual diversity